Special interest groups versus voters and the political economics of attention - Patrick Balles; Ulrich Matter; Alois Stutzer (University of Basel, Center of Business and Economics (WWZ), 2024)
We investigate whether US House representatives favour special interest groups over constituents in periods of low media attention to politics. Analysing 666 roll calls from 2005 to 2018, we show that representatives are more likely to vote against their constituency's preferred position the more special interest money they receive from groups favouring the opposite position. The latter effect is significantly larger when less attention is paid to politics due to distraction by exogenous newsworthy events like natural disasters. The effect is mostly driven by short-term opportunistic behaviour than the short-term scheduling of controversial votes into periods with high news pressure.
Keywords: D72; L82; L86; 330; Attention; campaign finance; interest groups; legislative voting; mass media; roll call voting; US House of Representatives